Politik Dinasti Dalam Kepemimpinan Desa Mangaledang Lama Kecamatan Portibi Kabupaten Padang Lawas Utara - Muhammad Taher Siregar; M. Arif Nasution; Marlon Sihombing (PERSPEKTIF, 2021)
The purpose of this study is to describe and explain the origins, causes and impacts of the emergence of dynastic politics in Mangaledang Lama Village, Portibi District, Padang Lawas Utara Regency. The form of this research is qualitative research with descriptive analysis, to describe and explain in depth the origins, causes and impacts of the dynastic politics. The result of the research states that starting from Daman Huri Siregar who was elected as village head from 2001 - 2011 (two periods), after that there was a desire to rule by passing his power to his own younger brother through the election of the village head. The contributing factor is the ownership of economic capital that is financially stable, has social capital such as a strong network among the community, has symbolic capital, namely the siregar clan which is known as the dominant ruling clan so that when compared to other clans, it is far less in number than the siregar clan. The impact is that power only circulates in the family itself, so that opportunities / opportunities for other people to get rights in the political and governmental sphere are not obtained. Therefore dynastic politics will be very detrimental to others and have an impact on a good system of government and a democratic system because opportunities for people who are capable and capable do not get opportunities in the political process.